Pengaruh Ukuran Perusahaan, Kompleksitas Operasi Perusahaan, Reputasi Auditor Dan Financial Distress Terhadap Audit Delay Studi Empiris Pada Perusahaan Sub Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2019-2022 - Putry Nurianti, Restika; Sosiady, Mulia; Ermansyah, Ermansyah (Basecamp Economics PubMed, 2024)
This research aims to determine the influence of company size, complexity of company operations, auditor reputation, and financial distress on audit delay in sub-food and beverage companies listed on the Indonesia Stock Exchange in 2019-2022. The population of this research is food and beverage subsector companies listed on the Indonesia Stock Exchange in 2019-2022. Using a purposive sampling method, 25 companies were selected as samples with 100 observations. This research uses a quantitative method using secondary data obtained from the Indonesian Stock Exchange. The data analysis tool uses eviews 12. Meanwhile, the data processing method used is panel data regression analysis. The results of this research show that the complexity of company operations, auditor reputation, and financial distress influence audit delay. Meanwhile, company size has no effect on audit delay.